A Digital Image Watermarking System: An Application of Dual Layer Watermarking Technique - Nurul Hidayah Ab Rahman; Noraini Che Pa; Ch’ng Chen Phin (Society of Visual Informatics, 2017)
Watermarking is a method to digitally sign a product to provide authentication and prevent copyright infringement to proving the ownership of a product and provides integrity for companies to protect their product. In this study, dual layer watermark that applies two different watermarking techniques at each layer is presented. The first layer applies the LSB Substitution technique while the second layer uses the Discrete Wavelet Transform (DWT) technique. This implies greater integrity as it contains of two signatures in providing authentication.